Deep shadows [large type] - Chapman, Vannetta (Bergren, Lisa Tawn. Remnants series., 2017)
"When a solar flare wipes out modern technology, Shelby Sparks becomes solely focused on providing for her diabetic son. Medication becomes a priceless commodity and the future resembles an apocalyptic nightmare"--